SARS-CoV-2: Pregnancy, Delivery and Postpartum. A short review. - Aguilar Uscanga, Blanca Rosa; Pérez-Elizondo, Sheila B.; Solis Aguilar, Jessica Guadalupe; Solis Pacheco, Josue Raymundo; Amézcua-López, Jesús Alonso; Martínez-Gómez, Celia Mariana (European Journal of Applied Sciences, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) is the ninth documented coronavirus to infect humans and it is highly transmissible; has caused a global pandemic and dramatic loss of human life worldwide. Isolated in Wuhan, China in late 2019, it struck nations with significant economic and public health consequences. The International Committee on Taxonomy of Viruses (ICTV) named the virus as SARS-CoV-2 and the disease as COVID-19. However, few studies have been published on the effects that this virus can have during pregnancy, childbirth and postpartum, so the objective of this review is to alert about the possible problems that women can present during their pregnancy, and provide adequate and specialized. It has been described that SARSCoV-2 virus has a predilection for the angiotensin converting enzyme (ACE) II receptor present in pneumocytes, enterocytes and at the placental level. Placental involvement could lead to hypoperfusion and thrombosis, resulting in fetal intrauterine growth restriction and preterm delivery. Careful monitoring of pregnant patients who test positive for SARS-CoV-2 is recommended because of the potential complications that could occur in the mother and fetus. The recommendations include offering vaccines against SARS-CoV-2 to pregnant and breastfeeding women, the provision of comprehensive health care to the mother-child pair; for example, maternal support networks and establishment of successful breastfeeding, which involves the development of the maternal-neonatal bond.